Eco-friendly, highly stable and efficient nanostructured p-type N-doped ZnO photocatalyst for environmentally benign solar hydrogen production - Bhirud, Ashwini P.; Sathaye, Shivaram D.; Waichal, Rupali P.; Nikam, Latesh K.; Kale, Bharat B. (Green Chemistry, 2012)
We have investigated an economical green route for the synthesis of a p-type N-doped ZnO photocatalyst by a wet chemical method. Significantly, hazardous H2S waste was converted into eco-friendly hydrogen energy using the p-type N-doped ZnO photocatalyst under solar light, which has previously been unattempted. The as-synthesized p-type N-doped ZnO shows a hexagonal wurtzite structure. The optical study shows a drastic shift in the band gap of the doped ZnO in the visible region (3.19-2.3 eV). The doping of nitrogen into the ZnO lattice is conclusively proved from X-ray photoelectron spectroscopy analysis and Raman scattering. The morphological features of the N-doped ZnO are studied from FESEM, TEM and reveal particle sizes to be in the range of similar to 4-5 nm. The N-doped ZnO exhibits enhanced photocatalytic hydrogen generation (similar to 3957 mu mol h(-1)) by photodecomposition of hydrogen sulfide under visible light irradiation, which is much higher as compared to semiconductor metal oxides reported so far. It is noteworthy that a green catalyst is investigated to curtail H2S pollution along with production of hydrogen (green fuel) using solar light, i.e., a renewable energy source. The green process investigated will have the potential to synthesize other N-doped metal oxides.

Environmentally benign enhanced H-2 production from abundant copious waste H2S using size tuneable cubic bismuth (Bi-0) quantum dots-GeO2 glass photocatalyst under solar light - Apte, Sanjay K.; Garaje, Sunil N.; Naik, Sonali D.; Waichal, Rupali P.; Kale, Bharat B. (Green Chemistry, 2013)
Hydrogen sulfide is a copious gas produced in refineries (15-20%) as well as billions of tons produced as a by-product in alkali industries. Selectively, only 5% has been utilised for the Claus process to produce liquid sulfur and it is also well known for its uneconomical and environmental problems. Here, we have demonstrated a significant green approach for conversion of poisonous H2S into H-2 by stable cubic bismuth (Bi-0) quantum dot-glass nanosystems using solar light as the energy source. Previously, metal oxides and sulfides have been demonstrated as solar light photocatalysts. However, a unique bismuth quantum dot-glass nanosystem has been designed where cubic phase bismuth quantum dots of size 1-2 nm are grown in the germanate glass matrix successfully. The presence of bismuth (Bi-0) was confirmed by XRD, Raman, TEM and X-ray photoelectron spectroscopy (XPS). The glass nanosystem shows quantum confinement with variation of the band gap from 2.95-1.51 eV. Considering the broad absorption from visible to near IR, we used this glass nanosystem as a solar light active photocatalyst and hydrogen production with respect to the quantum confinement of bismuth (Bi-0) quantum dots has been demonstrated for the first time. The photocatalytic activity for hydrogen production using glass nano-systems having bismuth quantum dot sizes of 1-2 nm and 3-6 nm was measured under solar light and prima fascia observations revealed that the glass nanosystems with very small quantum dots (1-2 nm) showed enhanced hydrogen evolution (11 541 mu mol h(-1) g(-1)) from H2S. The hydrogen evolution obtained is much higher than for previously reported visible light active nanostructured sulfide/oxide or embedded glass nanosystems. The glass nanosystems were also used for water splitting and show evolution of hydrogen without any co-catalyst. It is noteworthy that the quantum dot-glass photocatalyst is highly stable and catalyst regeneration is quite easy and fast. Hence, the QD-bismuth-glass nanocomposites have significant advantages over normal nanosized powder catalysts. Such unique glass nanosystems will also have great potential in photonics and optoelectronic applications.

Quantum confinement controlled solar hydrogen production from hydrogen sulfide using a highly stable CdS0.5Se0.5/CdSe quantum dot-glass nanosystem - Apte, Sanjay K.; Garaje, Sunil N.; Naik, Sonali D.; Waichal, Rupali P.; Baeg, Jin-Ook; Kale, Bharat B. (Nanoscale, 2014)
We have demonstrated unique CdS0.5Se0.5 and CdSe quantum dot-glass nanosystems with quantum confinement effect. The stable, monodispersed CdS0.5Se0.5 and CdSe quantum dots (QDs) of size 2 to 12 nm have been grown in a germanate glass matrix by a simple melt quench technique at moderate temperature. XRD and Raman studies show formation of hexagonal CdS0.5Se0.5 and CdSe in the glass matrix. The quantum confinement of CdS0.5Se0.5 and CdSe was studied using TEM and UV-Vis spectroscopy. The band gap of the glass nanosystem was tuned from 3.6 to 1.8 eV by controlling the CdS0.5Se0.5 quantum dot size in the glass matrix. It can be further tuned to 1.68 eV using growth of CdSe quantum dots in the glass matrix. Considering the tuneable band gap of the CdS0.5Se0.5 and CdSe quantum dot-glass nanosystem for the visible light absorption, a study of size tuneable photocatalytic activity for hydrogen generation from hydrogen sulfide splitting was performed under visible light irradiation for the first time. The utmost hydrogen evolution, i.e. 8164.53 and 7257.36 mu mol h(-1) g(-1) was obtained for the CdS0.5Se0.5 and CdSe quantum dot-glass nanosystems, respectively. The apparent quantum yield (AQY) was observed to be 26% and 21% for the CdS0.5Se0.5 and CdSe quantum dot-glass nanosystems, respectively. It is noteworthy that the present glass nanosystem as a photocatalyst was found to be very stable as compared to naked powder photocatalysts.

Studies on morphology of polyaniline films formed at liquid-liquid and solid-liquid interfaces at 25 and 5 A degrees C, respectively, and effect of doping - Waghmode, Babasaheb J.; Patil, Sagar H.; Jahagirdar, Mandar M.; Patil, Virendra S.; Waichal, Rupali P.; Malkhede, Dipalee D.; Sathaye, Shivaram D.; Patil, Kashinath R. (Colloid and Polymer Science, 2014)
It is well accepted that the morphology of the nanomaterials has great effect on the properties and hence their applications. Therefore, morphology of materials has become a focus of research in the scientific world. The present study shows that interfacial polymerization and subsequent self-assembly provides a control over the morphology, nanorod/nanosheet, of polyaniline (PANI) films synthesized by liquid-liquid interface reaction technique and solid-liquid interface reaction technique. The synthesized PANI films and its particulate structure are characterized by using various spectroscopic techniques such as UV-visible, ATR-IR, Raman and XPS. The study confirmed the formation, the structure, the size and shape of particles and morphology of PANI by using analytical techniques namely, SAED, SEM and TEM. An important observation is that doping with HCl significantly improves the nanorod formation at the interface. The doped PANI electrode exhibits a higher area with rectangular shape in CV cycle and better cycle stability when compared with the performance of undoped PANI films. We believe that the results of these studies can give valuable leads to manoeuvre formation of PANI films with desired morphology for various applications.
Keywords: interfacial polymerization; Liquid-liquid interface; Nanorods; nanosheets; polyaniline; Self-assembly; Solid-liquid interface; Thin films

Situ preparation of N-TiO2/graphene nanocomposite and its enhanced photocatalytic hydrogen production by H2S splitting under solar light - Bhirud, Ashwini P.; Sathaye, Shivaram D.; Waichal, Rupali P.; Ambekar, Jalindar D.; Park, Chan-J.; Kale, Bharat B. (Nanoscale, 2015)
Highly monodispersed nitrogen doped TiO2 nanoparticles were successfully deposited on graphene (N-TiO2/Gr) by a facile in-situ wet chemical method for the first time. N-TiO2/Gr has been further used for photocatalytic hydrogen production using a naturally occurring abundant source of energy i.e. solar light. The N-TiO2/Gr nanocomposite composition was optimized by varying the concentrations of dopant nitrogen and graphene (using various concentrations of graphene) for utmost hydrogen production. The structural, optical and morphological aspects of nanocomposites were studied using XRD, UV-DRS, Raman, XPS, FESEM, and TEM. The structural study of the nanocomposite shows existence of anatase N-TiO2. Further, the details of the components present in the composition were confirmed with Raman and XPS. The morphological study shows that very tiny, 7-10 nm sized, N-TiO2 nanoparticles are deposited on the graphene sheet. The optical study reveals a drastic change in absorption edge and consequent total absorption due to nitrogen doping and presence of graphene. Considering the extended absorption edge to the visible region, these nanocomposites were further used as a photocatalyst to transform hazardous H2S waste into eco-friendly hydrogen using solar light. The N-TiO2/Gr nanocomposite with 2% graphene exhibits enhanced photocatalytic stable hydrogen production i.e. similar to 5941 mu mol h(-1) under solar light irradiation using just 0.2 gm nanocomposite, which is much higher as compared to P25, undoped TiO2 and TiO2/Gr nanocomposite. The enhancement in the photocatalytic activity is attributed to `N' doping as well as high specific surface area and charge carrier ability of graphene. The recycling of the photocatalyst shows a good stability of the nanocomposites. This work may provide new insights to design other semiconductor deposited graphene novel nanocomposites as a visible light active photocatalyst.